Two-year clinical wear performance of two polyacid-modified resin composites (compomers) in posterior permanent teeth - Rafael Guerra Lund; Evandro Piva; Flávio Renato Reis de Moura; Flávio Fernando Demarco; Janaína de Oliveira Lima; Paulo Eduardo Capel Cardoso (Universidade Estadual de Campinas, 2016)
Aim: The aim was to compare the clinical wear of two compomers (F2000; 3M/ESPE and Dyract AP; Dentsply) placed in occlusal cavities in permanent molars within a two-year follow-up period using an indirect method of evaluation. Methods: Twenty-one patients, whose treatment plans included Class I restorations, were selected. Each patient received two occlusal Class I restorations in permanent molars. One and 2 years after placement of the restorations, the 21 teeth restored with each material were submitted to wear evaluation. Polyvinylsiloxane impressions were taken and casts were made (baseline, 1 year and 2 years). The casts were classified by comparative evaluation using sets of 18 calibrated standard models (0 to 900 ìm), according to Leinfelder's indirect method. Paired and unpaired t-tests were used for comparisons between the evaluations for the same material and between materials for each evaluation period, respectively. Results: The occlusal wear was higher afterAim: The aim was to compare the clinical wear of two compomers (F2000; 3M/ESPE and Dyract AP; Dentsply) placed in occlusal cavities in permanent molars within a two-year follow-up period using an indirect method of evaluation. Methods: Twenty-one patients, whose treatment plans included Class I restorations, were selected. Each patient received two occlusal Class I restorations in permanent molars. One and 2 years after placement of the restorations, the 21 teeth restored with each material were submitted to wear evaluation. Polyvinylsiloxane impressions were taken and casts were made (baseline, 1 year and 2 years). The casts were classified by comparative evaluation using sets of 18 calibrated standard models (0 to 900 ìm), according to Leinfelder's indirect method. Paired and unpaired t-tests were used for comparisons between the evaluations for the same material and between materials for each evaluation period, respectively. Results: The occlusal wear was higher after 2 years than after 1 year (p<0.001). The t-test demonstrated that the wear values, after 1 year, were similar for both compomers (F2000=17.6 ìm and Dyract AP=12.8 ìm). However, after 2 years, F2000 restorations (40.6 ìm) suffered significantly more wear (p<0.05) than Dyract AP restorations (29.8 ìm). Although compomers performed similarly after 1 year, Dyract showed less occlusal wear after 2 years. All occlusal Class I compomer restorations presented more occlusal wear after 2 years, but were considered as clinically acceptable within the evaluation period. Conclusions: The mean wear values found for both compomers do not indicate the need for either repair or replacement of the restorations. 2 years than after 1 year (p<0.001). The t-test demonstrated that the wear values, after 1 year, were similar for both compomers (F2000=17.6 ìm and Dyract AP=12.8 ìm). However, after 2 years, F2000 restorations (40.6 ìm) suffered significantly more wear (p<0.05) than Dyract AP restorations (29.8 ìm). Although compomers performed similarly after 1 year, Dyract showed less occlusal wear after 2 years. All occlusal Class I compomer restorations presented more occlusal wear after 2 years, but were considered as clinically acceptable within the evaluation period. Conclusions: The mean wear values found for both compomers do not indicate the need for either repair or replacement of the restorations.